ASSESSMENT OF PATIENTS' SATISFACTION IN MEDICAL AND SURGICAL WARDS IN A TERTIARY CARE HOSPITAL - Ahsan, Naveed; Chawala, Javed Akhtar; Farooq, Umer; Rasool, Ahsan; Ahmad, Ashfaq; Burki, Naveed Alam; Qureshi, Muhammad Umar (Journal of Ayub Medical College Abbottabad, 2012)
Background: Evolution is the natural process that is not limited merely to the biological world but to the social world as well. The standards of living and the expectations change with time. This study was done to generate data that can help doctors and hospital administration to identify and solve problems. Methods: It was a cross-sectional study conducted at a major tertiary care hospital of KPK through the month of July 2012. An interviewer based patient satisfaction questionnaire was used to estimate patients' satisfaction by asking questions regarding admission procedure, referral, clinical and lab investigation services, attitude of doctors and nurses, nursing services, cleanliness condition of the wards and overall level of satisfaction. Results: Study included 305 patients, 205 from surgical wards (144 males, 61 females) and 100 from Medical wards (52 males, 48 female). Satisfaction level was high among females than males. Most of the patients having low level of education and unemployed patients were satisfied. Cleanliness condition of wards and bathrooms was highly criticised. Attitude of doctors and nurses was much appreciated. About 70% of the patients were satisfied with explanation regarding their disease. More than half (59%) were not aware of post-surgical complications, and 67% were not aware of the use and possible side-effects of medication. About half of the patients couldn't utilise hospital lab. Overall satisfaction level was 68% in medical wards and 77% in surgical wards. Conclusions: Overall level of satisfaction was fair in both wards. Attitude of doctors and nursing staff was appreciated, but cleanliness conditions were criticised. There is a need for availability of free medicine and improvement of laboratory services and cleanliness. Keywords: Patients' satisfaction, Patients' experience, Quality of care